2015
DOI: 10.1177/1754337115582121
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oar-shaft stiffness and length on rowing biomechanics

Abstract: This work investigates the effects of oar-shaft stiffness and length on rowing biomechanics. The mechanical properties of the oar-shafts were examined using an end-loaded cantilever system, and theoretical relations were proposed between the mechanics of the oar-shafts and rowing performance. On-water experiments were subsequently conducted and rowing biomechanics measured via the PowerLine Rowing Instrumentation System. The PowerLine system measures force and oar angle on the oarlock, as well as proper boat a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…He reported that 'Shorter Oars Are More Effective'. However, Laschowski et al [9] studied experimentally the effect of oar-shaft stiffness and length with elite athletes. They showed that changes in stiffness and length of the oar led to small differences in the measured boat acceleration but these differences remained of the same order of magnitude as inter-stroke fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…He reported that 'Shorter Oars Are More Effective'. However, Laschowski et al [9] studied experimentally the effect of oar-shaft stiffness and length with elite athletes. They showed that changes in stiffness and length of the oar led to small differences in the measured boat acceleration but these differences remained of the same order of magnitude as inter-stroke fluctuations.…”
Section: Introductionmentioning
confidence: 99%